Study of Meibomian Gland Dysfunction in Patients Undergoing Cataract Surgery from Rural Ophthalmology Camps - Anand Murali; Malavika Krishnaswamy (Delhi Journal of Ophthalmology)
This study was performed to determine the prevalence of Meibomian Gland Dysfunction in patients undergoing cataract surgery at rural ophthalmology camps. McMonnies Dry Eye questionnaire was used to evaluate the symptoms. The patients were subjected to slit lamp examination, Schirmer’s Test, fluorescein staining and Tear film break-up time (TBUT). After examining 209 patients with varying cataract status, dry eye was found to have a prevalence of 37.8% with TBUT <10 seconds, but only 5.26% showed apparent signs of MGD. 33.5% subjects had a deficient aqueous component. The results suggest that the cause of dry eyes is not attributed to MGD.